2020
DOI: 10.1051/0004-6361/202037763
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strength of dust-ice mixtures and their relevance as cometary analog material

Abstract: Aims. The tensile strength of granular matter is of great importance to our understanding of the evolution of comets and to our attempts to reproduce processes on cometary surfaces in laboratory experiments. In this work, we investigate the tensile strength of three different materials and their mixtures, which can be used as cometary analog materials in the laboratory. Methods. We used two types of siliceous dusts and granular water ice whose polydisperse particles were either angular or spherical. Our sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 47 publications
3
36
1
Order By: Relevance
“…Previous experimental work has shown that at temperatures of 150 K and below, the tensile strength of water ice is much lower than previously expected (Gundlach et al 2018a;Musiolik & Wurm 2019). Haack et al (2020) extended these experiments and investigated different mixtures of dust and water ice for their suitability as comet analogs and found that the tensile strength of a mixture is dominated by the component with the highest tensile strength. In this work, we use these mixtures to study the morphological evolution of samples in a vacuum sublimation chamber with the aim of reproducing basic morphological structures observed at the surface of 67P.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Previous experimental work has shown that at temperatures of 150 K and below, the tensile strength of water ice is much lower than previously expected (Gundlach et al 2018a;Musiolik & Wurm 2019). Haack et al (2020) extended these experiments and investigated different mixtures of dust and water ice for their suitability as comet analogs and found that the tensile strength of a mixture is dominated by the component with the highest tensile strength. In this work, we use these mixtures to study the morphological evolution of samples in a vacuum sublimation chamber with the aim of reproducing basic morphological structures observed at the surface of 67P.…”
Section: Introductionmentioning
confidence: 82%
“…1). Additionally, it is possible to produce samples with a very low tensile strength with these spherical particles (Haack et al 2020) to simulate the low tensile strength of cometary materials (Groussin et al 2015;Attree et al 2018). The filling fraction of the samples describes how much free space is in a volume filled with particles and is with ∼0.4 (Fig.…”
Section: Selection Of Materialsmentioning
confidence: 99%
See 3 more Smart Citations